Management of Bio-Waste by the Paper Mulch - Mohebi, Zahra (Universitas Diponegoro, 2021)
Mulch is a type of protective covering placed on or spread over the soil surface that helps to conserve soil moisture, suppress weed growth and enrich the soil. The paper mulch is the most complete mulch and has numerous beneficial effects upon the soil and plants. This mulch which is produced from office waste paper, newspaper and wrapping papers, conserves soil moisture, is effective at suppressing and inhibiting weed growth, enhances agro-ecosystem health by improving the air and water movement through the soil; providing moist conditions thereby promoting micro-organisms and worm populations; promoting plant growth and product, promoting leaf litter build up and helping to improve the pH balance in the soil.